Empleo de la caña de azúcar (Saccharum officinarum) en la elaboración de saccharina rustica para alimentación en bovinos - Alvarado Anchundia, Lisbeth Mayerly (2022)
This document allowed to know relevant information on the manufacture of saccharina rustica as an alternative feed for cattle, especially in times when there is a shortage of grass. This technology is normally developed by the rancher of the coastal region, which is where this sugar cane crop is adapted due to the favorable environmental conditions for it. The saccharina rustica is made by crushing the stems of the sugar cane devoid of leaves, to then be layered on a cement or plastic surface and additives such as mineral salt and urea are added and mixed together. , to then let it carry out its fermentation process for a period of 12 hours and this process is carried out twice so that the added additives are compacted in a homogeneous way and have a saccharin with a high nutritional content. Based on the results obtained, it was possible to show that livestock producers, mainly from the coastal region, use this technology to supply necessary food for livestock since it has a large amount of nutrients, which leads to a gain in weight of cattle. There are multiple benefits obtained from the production of saccharina rustica, food can be provided to livestock throughout the year as long as the farmer has sugar cane, it is easy to prepare, it is inexpensive and food can be saved for throughout the year, especially in times of drought.